Managing Independence in Curriculum Design to Optimize Differentiated Learning: A Systematic Review - Siti Halimah; Muhammad Nurwahidin; Siti Rahma Sari (Journal of Educational Management Research, 2025)
This study examines the role of Merdeka (Independent) Curriculum management in enhancing the effectiveness of differentiated learning in Indonesian schools. Curriculum management plays a pivotal role in improving education quality, particularly in the implementation of the Independent Curriculum, which grants flexibility to tailor learning to individual student needs. Differentiated learning fosters inclusive, adaptive, and responsive classrooms that address diverse abilities, interests, and learning styles. Using a Systematic Literature Review (SLR) guided by the PRISMA framework, this research analyzed 20 peer-reviewed articles published between 2019 and 2024 from Google Scholar and SINTA. Findings reveal that the Independent Curriculum’s flexible, student-centered approach significantly supports differentiated learning, improving student engagement and enabling teachers to adapt instruction effectively. However, challenges remain, including varying levels of teacher preparedness and the complexity of addressing diverse learner profiles. Addressing these issues requires targeted professional development and sustained teacher support. Overall, this review highlights how Independent Curriculum management contributes to more active, personalized learning experiences, ultimately advancing educational inclusivity and responsiveness in Indonesia.